Isolation of Methyl Gallate from Toxicodendron sylvestre and Its Effect on Tomato Bacterial Wilt - Yuan, Gao-Qing (Plant disease, 2012)
We determined that the methanol extract of Toxicodendron sylvestre could significantly inhibit Ralstonia solanacearum in vitro and in planta. One compound responsible for the antibacterial activity was isolated from the ethyl ether extract and identified as methyl gallate (MG) based on its 1H and 13C nuclear magnetic resonance data as well as mass spectroscopy. MG displayed broad-spectrum activity against plant-pathogenic bacteria, and strong inhibitory effects on the growth of plant-pathogenic oomycetes. The half inhibition concentration of MG on R. solanacearum was 8.3 mg/liter, which was tested by the agar dilution method. Disease control trials in planta showed that both natural and synthetic MG could effectively reduce the incidence of tomato bacterial wilt, and there was no significant difference between them in control efficacy. This is the first report on the use of MG for the control of a plant bacterial disease. Because of its broad-spectrum antimicrobial activity and significant control efficacy on tomato bacterial wilt in planta, MG shows potential to be used as a bactericide to control plant bacterial wilt